Dramatic effects but fast adaptation: Changes in life satisfaction and different facets of affective well-being around the death of a partner and death of a child - Eva Asselmann; Jule Specht (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Although everyone would agree that bereavement is extremely stressful, surprisingly little is known about changes in different facets of affective well-being in the years surrounding the death of a loved one. On the basis of the Socio-Economic Panel Study, we examined changes in cognitive well-being (life satisfaction) and different facets of affective well-being (happiness, sadness, anxiety, and anger) in the years around the death of a partner (N =989) and child (N =276). Data on the death of a partner and child as well as cognitive and affective well-being were assessed yearly since 2007. Multilevel analyses revealed that both events were associated with very large well-being impairments (>1 SD) that were most pronounced for sadness, happiness, and life satisfaction in the first year of bereavement. Afterwards, bereaved individuals managed to recover impressively well: Levels of life satisfaction, happiness, and sadness were on average similar 5 years after losing a partner or child compared with 5 years before the respective loss. Our findings suggest (a) that many individuals tend to be capable to even cope with highly stressful loss experiences and (b) that Set-Point Theory not only applies to life satisfaction but also different facets of affective well-being around the death of a loved one.
Keywords: 330; affect; bereavement; grief; life satisfaction; widowhood